Population and Development Planning (PDP) Model: The 1998 Update - Aniceto Jr. C. Orbeta; Mildred Belizario; Edith Lavina (Philippine Institute for Development Studies (PIDS), 1999)
This paper presents an update of the Population and Development Planning (PDP) model. The PDP model is an economic-demographic model designed to capture the long-term interactions between economic and demographic variables. Also presented in the paper are results of diagnostic and policy simulation runs.
Keywords: 330; economic/development modelling; demographic economics